Asia, the US and extended nuclear deterrence atomic umbrellas in the twenty-first century - O'Neil, Andrew (Routledge, Taylor & Francis Group, 2013)
"Since the end of the Cold War, significant attention has focussed on the issue of nuclear deterrence and in particular whether formal nuclear security guarantees from nuclear weapons states to non-nuclear weapons states involving the possible use of nuclear weapons have a place in the twenty-first century global strategic landscape. Growing support for nuclear disarmament in the US and elsewhere has seen witnessed serious doubts being raised about the ongoing utility of extended nuclear deterrence. This book provides the first detailed analysis of the way in which extended nuclear deterrence operates in contemporary Asia. It addresses the following key questions: What does the role of extended nuclear deterrence in Asia tell us about the broader role of extended nuclear deterrence in the contemporary international system? Is this role likely to change significantly in the years ahead? O'Neil uses a theoretical and historical framework to analyse the contemporary and future dynamics of extended nuclear deterrence in Asia and challenges many of the existing orthodox perspectives on the topic"--Provided by publisher.